Hba1c and Blood Pressure Correlation In Patients With Uncontrolled Type 2 Diabetes Mellitus - Adang Muhammad Gugun; Suryanto Suryanto; Muhammad Emil Fadli Nugroho; Pravda Bintang Bari (International Journal of Health and Pharmaceutical (IJHP), 2025)
The primary metabolic disorder in diabetes mellitus is hyperglycemia, which can be assessed through glycated hemoglobin (HbA1c) levels as an indicator of long-term blood glucose control. Abnormal glucose metabolism may affect vascular function and contribute to increased blood pressure, making hypertension a common complication among patients with uncontrolled diabetes mellitus. This study aimed to determine the correlation between HbA1c levels and blood pressure in patients with uncontrolled type 2 diabetes mellitus. An observational cross-sectional study was conducted at RSU PKU Muhammadiyah Gamping involving 90 subjects aged 31–65 years, consisting of 48 men and 42 women. HbA1c levels were measured using the boronate affinity method, and blood pressure was assessed with a sphygmomanometer. Statistical analysis used the independent t-test, Mann–Whitney U test, and Spearman correlation with a significance level of α = 0.05. The mean HbA1c level was 10 ± 2.08%, mean systolic pressure 132.75 ± 18.04 mmHg, and mean diastolic pressure 83.28 ± 10.38 mmHg. Hypertension occurred in 36.66% of subjects. The results showed no significant differences in blood pressure between sexes or glycemic control groups and no significant correlation between HbA1c levels and blood pressure. These findings suggest that factors other than glycemic control may influence blood pressure in diabetic patients.